Choice Overload and Partial Season Ticket Sales - Clinton J. Warren; Joshua M. Lupinek (Journal of Applied Sports Management, 2019)
This study utilizes a consumer choice experiment to assess if choice overload exists with partial season ticket packages of a Major League Soccer (MLS) team. Individuals were randomly assigned to one of three conditions with an increasing number of partial season ticket options. Study results indicate as the number of options available increases, buyers are more likely to feel the decision-making process was difficult and regret the decision they made. However, participants were generally satisfied to be afforded so many options, and increasing the number of ticket plan options did not appear to affect purchase intent or potential purchase satisfaction.
Keywords: Choice overload; consumer choice; experimental design; marketing; ticket sales